Synthesis of electrode materials for aluminium aqueous batteries - Tan, Ivan Fu Xing (2019)
Ever since the lithium ion battery was commercialised by Sony Corporation in 1991, the use of lithium-ion batteries has been widespread in the modern world to power various devices such as mobile phones and laptops.[1, 2] Lithium ion and nickel-cadmium batteries broke into the industry in the 1990s and were the main competitors for mainstream rechargeable battery use. Advantages of the lithium ion battery over nickel-cadmium were many, including a high energy density, lower self-discharge, and minimal damage to the environment when disposed.[2] There is however, always a need to search for cheaper, safer or more efficient alternatives. As an alkali metal, lithium is generally considered as a reactive metal, which gives rise to safety concerns for the manufacturing process and general consumer usage. Considering the widespread use of lithium ion batteries today, this will eventually lead to a depletion of our lithium resources. This further reinforces the need for research to be carried out in the development of future replacement battery systems. A battery that is large in capacity, supports a large number of charge cycles, all at the lowest cost possible, can prove to be an effective replacement. There is hence a need to investigate the viability of the use of aluminium in aqueous batteries. The aim of the project was the synthesis of optimal electrodes from the evaluation of various feasible materials through testing of the synthesised batteries in practical use. This was achieved through the assessment of multiple factors and specifications, including capacity, number of charging cycles, shelf life and charging time.